Natural Convection in a Concentric Annulus: A Lattice Boltzmann Method Study with Boundary Condition-Enforced Immersed Boundary Method (Advances in Applied Mathematics and Mechanics, 2013)
In this paper, a boundary condition-enforced IBM is introduced into the LBMin order to satisfy the non-slip and temperature boundary conditions, and naturalconvections in a concentric isothermal annulus between a square outer cylinder and acircular inner cylinder are simulated. The obtained results show that the boundarycondition-enforced method gives a better solution for the flow field and the complicatedphysics of the natural convections in the selected case is correctly captured. Thecalculated average Nusselt numbers agree well with the previous studies.